Probabilistic bidding model - Veravit Sattayanon; Ping Kunawatsatit; Jearkjirm, Vithool; Chauhan, Roshan Lal; The Australian Government (Bangkok : Asian Institute of Technology, 1984)
The research is to determine whether it seems feasible to apply the probabilistically model to illustrate the linkage of the bidding situation, and other interacting factors to the bidding price of any types and scales of construction works. The models will be constructed from the actual statistical data. Analysis and evaluation of the data to the model will b e shown . The scope of this research is limited by using data on construction projects in Thailand in the period of the last four years. The model constructed can be used to determine a bidding price for a contractor to win the bid at various conditions. In addition to the direct benefit from the model e valuation, the forecasting property will help the contractor to make reasonable plans. Using this model, it is expected that a contractor could bid his projects with the least degree of risk. Consequently, the rate of failure could then be reduced.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1984
Keywords: Letting of Contracts